Knygos vaidmens kaita visuomenėje - Zinkevičienė, Julija (Knygotyra, 2005)
During different periods, a book played a different role in the life of society, depending on social, economic, and cultural conditions.The article seeks to analyze the role of a book as a document in several aspects: the book as a document, changes in its structure and carrier, changes in its functions during different periods, and the advantages and shortcomings of printed and electronic books. The place of a book within the system of mass media and its future is also discussed.A document, as a source of knowledge, is a unity of content and form. Research has mainly directed attention to the most important forms of documents. A book became the main object of research not because it is a printed item, but because it has dominated the system of documentary communication.The development of science and technology gave birth to new carriers of information and changed the traditional information environment into a virtual one, along with the material form of a document. The document consists of three components: information, a carrier, and technology for recording the information on the carrier (including technology for document identification). Two of these components may differ: the material form turns into a digital form, which exists in a virtual environment. The structure of the document changes from linear to digital. The social and economic environment is characterized by lowered production costs. Quicker and simpler technological processes attract a significant part of society.For a long time, the term "book" was used generally to denote documents. However, a book has its own specific features and differs from other documents. The book is characterized by two aspects: content and form. Content includes the essence of a book, such as ideas and thoughts. The form is the material environment that transfers and preserves information. A book is one of the most popular and oldest types of documents and has a unique place in society and history.It is claimed that the role of books in human life diminishes; however, a book is something continuous that stays with a person from childhood to old age. Some years ago, a book was revived and prepared for a new life. Its form and existence will depend on the social, economic, and cultural environment. The market will also influence how electronic and printed books will continue to exist.A book remains a guarantor of stability, cultural value, historical heritage, and its form, structure, functions, and role will become clearer in the future.